Comparative study of two potential recuperating converters in DC railway electrification system for harmonic mitigation - Z. H. Choi; C. L. Toh; M. H. Z. Hilmi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The regenerative braking energy produced by Light-Rail-Transit (LRT) train is commonly transferred back to power grid via a conventional three-phase inverter (recuperating converter). Although this is a cost saving solution but the ac grid current and voltage waveforms were distorted. Hence passive filters are integrated to mitigate the harmonics. This paper proposed to replace the conventional inverter system with a multilevel converter. Cascaded H-Bridge (CHB) converter and Modular Multilevel Converter (MMC) are selected to be evaluated in this paper due to their modularity structures. The aim of this study is to determine the most potential multilevel converter to be implemented without additional passive filters. Nine-level CHB and nine-level MMC converters are modeled with MATLAB/Simulink simulation tool. Both converters are modulated with Level-Shifted Pulse Width Modulation technique. The output voltage and current waveforms generated by CHB and MMC are presented with full analysis. It is concluded that MMC converter is more suitable to be used as a recuperating converter. It produces a clean voltage and current waveforms. The voltage and current Total Harmonic Distortion (THD) indexes are found approximate to 8% and 3%.